A cylinder model for characterization of deformation and damage development in a unidirectional composite. - Luo, J. J.; Daniel, I. M.
A cylinder model is proposed to provide the framework of stress analysis for multiple-fiber or matrix-fracture problems in unidirectional composites under longitudinal tension. On the basis of assumptions of axisymmetric displacement fields, the principle of virtual work is applied and governing equations are derived. The equations lead to a general correlation between macroscopic and microscopic deformation of damaged composites. The results are independent of fiber/matrix interface bonding conditions. The theory is applied to the damage development of unidirectional brittle-matrix composites. The transverse strain reversal phenomenon is explained by the model as the direct result of underlying mechanics of damaged composites, and thus can be used to help identify the microscopic damage development. The calculation suggests that interface debonding occurs along with matrix cracking, possibly with some delay, followed by interface crack opening after debonding.
Keywords: A. CERAMIC-MATRIX COMPOSITES; B. FIBRE/MATRIX BOND; B. INTERFACE; C. DAMAGE MECHANICS; C. DEFORMATION